Avaliação funcional da interação entre os núcleos da rafe e o núcleo retrotrapezóide nas respostas ventilatórias à hipercapnia em ratos - Leirão, Isabela de Paula (2020)
During hypercapnia, chemosensory cells located in the brainstem are stimulated and send excitatory inputs to the respiratory network to promote an increase pulmonary ventilation. Among the candidates responsible for central chemoreception are the raphe serotonergic neurons, which widely send projections to distinct respiratory compartments. In spite of the anatomical evidence, there are few functional studies demonstrating how the raphe serotonergic neurons interact with the respiratory network, specially other chemosensitive sites. Herein, we explored the hypothesis that the ventilatory response to hypercapnia depends, at least in part, on the stimulation of the raphe serotonergic neurons that send projections to the retrotrapezoid nucleus (RTN) - an important respiratory region of the ventromedullary surface that contains CO2/pH sensitive cells. To reach this goal, the pulmonary ventilation was evaluated under baseline conditions and during the exposure to hypercapnia in unanesthetized juvenile Holtzman rats (60 - 90 g) that received bilateral microinjections of the toxin anti-SERT-SAP (0.1 mM) in the RTN to selectively lesion serotonergic neurons that send projections to this region. Fifteen days after microinjections of anti-SERT-SAP in the RTN (n = 8), baseline respiratory frequency (f) and tidal volume (VT) were not different from control animals that received vehicle microinjections (n = 9). On the other hand, the specific ablation of RTN-projecting serotonergic neurons markedly attenuated the response of increase in the f, but not in the VT, observed during the exposure to 7% CO2. The impaired tachypneic response to hypercapnia induced by anti-SERT-SAP microinjections in the RTN was associated with reduced number of serotonergic neurons in the raphe obscurus and magnus, but not in the raphe pallidus. Our data support the idea that, in the absence of anesthesia, the activation of part of medullary raphe serotonergic neurons that send projection to the RTN are necessary for the processing of ventilatory reflex responses during the exposure to high CO2.